Critical behavior of La-0.67(BaxCa1-x)(0.33)MnO3 perovskites (0 <= x <= 1) - Panagiotopoulos, I.; Moutis, N.; Stamopoulos, D.; Niarchos, D.; Pissas, M. (PHYSICA B, 2000)
The magnetic critical behavior in the series La-0.67(BaxCa1-x)(0.33)MnO3 (0 less than or equal to x less than or equal to 1) of manganese perovskites is studied by means of DC magnetic measurements. As Ca ions are substituted by the larger Ba ions, the transition temperature increases from 265 to 340 K as a result of structural changes. Arrott plots show that only in samples with x greater than or equal to 0.25 the magnetic properties follow the behavior expected for a conventional second-order ferromagnetic transition. The values of critical exponents (beta, gamma) estimated by modified Arrott plots are found to lie between those predicted for a 3D-Heisenberg model and those of mean field theory. (C) 2000 Elsevier Science B.V. All rights reserved.